Law and features of TVOC and Formaldehyde pollution in urban indoor air. (May 2016) - Chi, Chenchen; Chen, Weidong; Guo, Min; Weng, Mili; Yan, Gang; Shen, Xueyou
Abstract: There are several categories of indoor air pollutants. Organic pollutants are the most common ones. This study chooses TVOC and Formaldehyde, two of the typical pollutants, as indicators of evaluating household indoor air pollution and improves the TVOC concentration prediction model through the samples of indoor air taken from 3122 households. This study also categorizes and explains the features of household indoor air pollution based on the TVOC and Formaldehyde models as well as a large amount of sample measurement. Moreover, this study combines the TVOC model with the Formaldehyde model to calculate and verify the critical values of each type of indoor air pollution. In this study, indoor air pollution is categorized into three types: decoration pollution, consumption pollution and transition pollution. During the first 12 months after decoration, decoration pollution is the primary pollution type, both TVOC and Formaldehyde are highly concentrated while sometimes seriously over the standard. Pollutants mainly come from volatile sources. After the first 12 month but before 24 months the indoor air pollution is transition pollution. Both decoration materials and human activates affect the indoor air quality. 24 months after decoration, it transits into consumption pollution. In this stage, the main pollutants come from combustion sources, and concentration of pollutants fluctuates with the appearance and disappearance of the sources. Graphical abstract: Highlights: We complement the data of TVOC and HCHO concentrations with 3122 sample number. We categorize indoor air pollution into three types and explain the features. We improve the TVOC prediction model with consideration of source feature factor. We combine TVOC model with HCHO model to clear the critical value of three types.